A Robust Scheme for Coherency Detection in Power Systems - Adom-Bamfi, Gideon; Frimpong, Emmanuel Asuming (JURNAL NASIONAL TEKNIK ELEKTRO, 2021)
This paper presents an approach for online generator coherency identification based on windowed dynamic time warping (DTW). Generator rotor speed deviations measured by phasor measurement units (PMUs) are used as input data to compute a DTW dissimilarity matrix. Using the dissimilarity matrix together with Agglomerative Hierarchical Clustering (AHC) and Hubert-Levin index (C-index), generators are optimally grouped into coherent clusters. In addition to the clustering of generators, an index for characterizing the transmission delay of a Wide Area Measurement System (WAMS) is presented. A data delay factor that can indicate whether there is an inconsistent PMU data transmission delay is also proposed. The coherency identification technique and indices were tested using simulations carried out on the IEEE 39-bus system. The test results indicate that the proposed scheme accurately clusters generators into coherent groups. The suggested indices were also found to be valid.Â Keywords :Â coherence identification, dynamic time warping, speed deviation, phasor measurement unit, dissimilarity matrix